2023
DOI: 10.1002/prop.202300018
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and Perturbative Analysis of Some Newly Developed F(R,Lm,T)$\mathcal {F}(R,L_m, T)$ Theories Under the Scenario of Conserved Energy‐momentum Tensor

Abstract: The present work is devoted to explore some interesting cosmological features of a newly proposed theory of gravity namely theory, where R and T represent the Ricci scalar and trace of energy momentum‐tensor, respectively. First, a non‐equilibrium thermodynamical description is considered on the apparent horizon of the Friedmann's cosmos. The Friedmann equations are demonstrated to be equivalent to the first law of thermodynamics, i.e., , where refers to entropy production term. The constraint for validity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Also, in geometry-matter couplings [16], it is shown that the matter content of the wormhole is remarkably able to obey the energy conditions. There are a number of modified gravity theories that have been proposed in the literature [17][18][19][20][21][22][23][24][25][26][27][28][29] to get around the undetectable exotic matter.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in geometry-matter couplings [16], it is shown that the matter content of the wormhole is remarkably able to obey the energy conditions. There are a number of modified gravity theories that have been proposed in the literature [17][18][19][20][21][22][23][24][25][26][27][28][29] to get around the undetectable exotic matter.…”
mentioning
confidence: 99%
“…Substituting the value of c 1 in equation (21) we get, graphical representation is shown in the figure1. Now, the incorporation of equation(23) into equations (17)-(19) for the NEC regarding radial and tangential pressures at the throat r = r 0 can be uniquely expressed as By performing another integration on equation(20) with α = 3 to determine the shape function b (r), using the throat condition b(r 0 ) = r 0 , we arrive at the following result…”
mentioning
confidence: 99%